Mites (Acari) inhabiting Jatropha curcas L. (Euphorbiaceae) crops: The role of seasonality and weeds - Rezende, José M. [UNESP]; Verona, Rodrigo L. C.; Lofego, Antonio C. [UNESP] (Systematic and Applied Acarology Society, 2016)
Mite communities inhabiting crops are influenced by several environmental factors, e.g. rainfall, seasonality and the presence of weeds within the plantation. In this study, we seek to clarify the seasonality patterns of mite communities present in physic nut crops, Jatropha curcas L. (Euphorbiaceae), by evaluating the influence of these factors on the most abundant species found. We verified that Polyphagotarsonemus latus Banks (Tarsonemidae) and Tetranychus bastosi Tuttle, Baker & Sales (Tetranychidae), the most abundant phytophagous species, had random seasonality patterns in the physic nut crops. In the field, predatory species of natural occurrence were not able to control the population growth of phytophagous mite species. Also, the presence of weeds among physic nut crops increased the number of potential predators and the diversity of mite species in the agroecosystem.
Keywords: Agroecology; biodiesel production; Tarsonemidae; Tetranychidae